Answer:
x₁ = 6 and x₂ = 8
Step-by-step explanation:
See the picture below
Answer:
z=-3
Step-by-step explanation:
-5z+9=24 so, subtract 9 from both sides becuase of liked terms to get -5z=15, then divide both sides by -5 to get z = -3 hope it helps:)
<2,14> thats the answer its complicated but i got it after the 2nd try
Answer: D. (x-6)(x-6)
Step-by-step explanation:
We have the following trinomial, which is also known as perfect square trinomial, because the first and the third term are squares:
(1)
First term:
Third term:
If we factorize this expression we have:
As we can see, the trinomial (1) has two factors:
and
Therefore, the correct option is D.